Effect of Hydraulic Retention Time on the Treatment of Pulp and Paper Industry Wastewater by Extended Aeration Activated Sludge System - Jagaba, A.H. (Institute of Electrical and Electronics Engineers Inc., 2021)
The pulp and paper industry produce dark-colored effluent with high levels of organic matter and nutrients. As a result, a biological treatment system consisting of an aeration tank containing 3.5-6 g/L starting biomass and a clarifier chamber was set up in this investigation. After acclimation, the reactor was driven at a flow rate of 5 L/day for a few weeks at 48h, 24h, and 12h HRT. All through the investigation, the concentrations of organic and nutrient parameters are measured in the influent and effluent samples and documented for data processing. The results reveal that ammonia has satisfactorily met the Standard 'A' standard limits of 10 mg/L after 24 hours of HRT. As a result, reduction efficiencies for nitrate and COD were 80.5 and 95, respectively. Surprisingly, the majority of the effluent COD readings met the acceptable standard, so no additional testing is required. The mean BOD concentration in effluent was found to be 4.54 mg/L. Â© 2021 IEEE.